Criticism of Contributory Negligence in Contracts Law in Iran and America - mozhdeh zafari; Morteza Shahbazinia; MEHRZAD ABDALI; Seyyed Elham-aldin Sharifi (پژوهشهای حقوقی)
When the obligee does not collaborate with the obligor based on good faith in any steps of the contract including formation and execution or even after contract breach and this causes or increases losses, then that situation gives rise to the concept of the fault of the injured party. Therefore, if the obligee and the obligor jointly cause or increase losses, then the concept of contributory negligence, or comparative negligence according to the US legal system, should be considered. The present paper aims to conduct a comparative study on contributory negligence in contract law together with an analysis of relevant domestic and foreign opinions. It is concluded that in the US legal system, contributory negligence is usually dismissed in the field of contracts; but "reasonable reliance" and "predictability" have efficient similarities to the contributory negligence concept and this fact reveals traces of contributory negligence in the US legal system. However, in the Iranian legal system laws indirectly imply this concept and the presence of contributory negligence in the Iranian law can also be confirmed based on analogy, ascertainment, good faith, and purpose of law and the fact that this concept merely mentioned with regard to some laws, can be explained based on the Islamic prevalence rule (Qalabah).